Approaches to Learning at Work: Investigating Work Motivation, Perceived Workload, and Choice Independence. (August 2013) - Kyndt, Eva; Raes, Elisabeth; Dochy, Filip; Janssens, Els
Learning and development are taking up a central role in the human resource policies of organizations because of their crucial contribution to the competitiveness of those organizations. The present study investigates the relationship of work motivation, perceived workload, and choice independence with employees' approaches to learning at work. Participants in this study were 358 Belgian employees who completed the Approaches to Learning at Work Questionnaire, the Workplace Climate Questionnaire, and the Motivation at Work Scale . Results show that both autonomous and controlled motivation relate positively to employees' deep approaches to learning. In addition, an interaction effect of perceived workload and choice independence on a deep approach to learning was found. The results concerning a surface-disorganized approach to learning showed a negative relationship with autonomous motivation and a positive relationship with perceived workload. None of the predictors related significantly to a surface-rational approach.